Development of ethnoscience-loaded e-modules to improve student learning outcomes on environmental change materials - Lestiani, Salsa Fani; Gloria, Ria Yulia; Mulyani, Asep (IAIN Palangka Raya, 2025)
This study aims to produce a product in the form of an electronic module (e-module) containing ethnoscience in a flipbook format using the Heyzine website for environmental change material that is feasible, effective, and practical for improving student learning outcomes. The research method used in this development is Research and Development (R&D) with the 4D development model: define, design, develop, and disseminate. The ethnoscience-loaded e-module was tested on 108 tenth-grade high school students in Majalengka Regency. The research results show that the developed ethnoscience-loaded e-module (1) has very high feasibility based on expert validation of content feasibility, language, presentation, learning support, screen design appearance, ease of use, usefulness, and graphics; (2) has moderate effectiveness based on the n-gain of student learning outcomes; (3) has very positive practicality based on student responses, indicating that the e-module is very engaging for use in learning. The ethnoscience-loaded e-module on environmental change material to improve student learning outcomes is feasible, effective, and practical. Further studies are needed to test the application of the e-module in various school contexts and to explore the use of platforms other than Heyzine.